2009
DOI: 10.1016/j.commatsci.2009.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of delamination in CFRP laminates: Effect of microstructural randomness

Abstract: Due to their high specific strength and stiffness, fibre-reinforced composite materials are being increasingly used in structural applications where a high level of performance is important (e.g. aerospace, automotive, offshore structures, etc.). Performance in service of these composites is affected by multi-mechanism damage evolution under loading and environmental conditions. For instance, carbon fibre-reinforced laminates demonstrate a wide spectrum of failure mechanisms such as matrix cracking and delamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
(16 reference statements)
0
14
1
Order By: Relevance
“…More detailed analyses were performed based on three-dimensional models and a number of statistical realizations based on a half-scatter of 50% of fracture energy were presented. In contrast to the two-dimensional analyses reported previously [8], the results here showed lower load-bearing capacities for most of the random models than that in the uniform model. Also, the damaged area and the crack lengths also showed higher values in the random realizations compared to the uniform case above a certain value of applied displacement.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…More detailed analyses were performed based on three-dimensional models and a number of statistical realizations based on a half-scatter of 50% of fracture energy were presented. In contrast to the two-dimensional analyses reported previously [8], the results here showed lower load-bearing capacities for most of the random models than that in the uniform model. Also, the damaged area and the crack lengths also showed higher values in the random realizations compared to the uniform case above a certain value of applied displacement.…”
Section: Discussioncontrasting
confidence: 56%
“…A considerable difference in the values of reduction in stiffness between cases with different crack spacings suggested that the assumption of averaged distributions of defects can lead to unreliable predictions of structural response. In another work by Khokhar et al [8], based on twodimensional DCB models, it was concluded that the variation in the fracture properties undertaken to analyze the effect of material randomness using stochastic cohesive zone elements had a potentially significant effect on the predictions of the performance of CFRP laminates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the application of CZE requires a fine spatial discretization at the cohesive zone to capture the damage growth properly. However, such refinement may be prohibitive since it needs a significant increase in computational efforts [26]. An optimum number of elements are required in the cohesive zone to obtain accurate numerical results.…”
Section: Discretization and Mesh Convergencementioning
confidence: 99%
“…Case C. Model with one crack and cohesive elements between 0 o and 90 o layers using random fracture properties based on a 2-parameter Weibull's distribution [8] (multiple realizations presented). A value of half scatter of 50% of properties is selected to underline the effect of the material's stochastic nature on the course of damage initiation and propagation.…”
Section: Matrix Cracks As Initiation Points For Delaminationmentioning
confidence: 99%